Changes in Green Space Use During a COVID-19 Lockdown Are Associated With Both Individual and Green Space Characteristics - Berdejo-Espinola, Violeta; Zahnow, Renee; Suárez-Castro, Andrés F.; Rhodes, Jonathan R.; Fuller, Richard A. (Frontiers in Ecology and Evolution, 2022)
Mobility restrictions imposed during the COVID-19 pandemic present a useful study system for understanding the temporal and spatial patterns of green space use. Here, we examine green space characteristics and sociodemographic factors associated with change in frequency of green space use before and during a COVID-19 lockdown in Brisbane, Australia drawing on a survey of 372 individuals. Applying regression analysis, we found that individuals who visited a different green space during lockdown than before tended to decrease their frequency of visits. In contrast, individuals who continued visiting their usual green space during lockdown were more inclined to increase their number of visits. Changes in frequency of green space use were also associated with particular characteristics of their usually visited green space. The presence of blue spaces and accessibility (carparks/public transport) were associated with increased frequency of use while foliage height diversity was associated with reduced frequency of use. We found that females were more likely to change their green space visitation frequency during COVID-19 compared to men and they also reported greater importance of green spaces for social and family interactions and spiritual reasons during COVID-19 compared to before. Males showed greater increases than females in the importance of green space for nature interactions and mental health benefits during the COVID-19 lockdown compared to before. Our results provide key insights for future resilient urban planning and policy that can fulfil a wide range of physical and psychological needs during a time of crisis and beyond.